Analyzing torquoselectivity in electrocyclic ring opening reactions of trans-3, 4-dimethylcyclobutene and 3-formylcyclobutene through electronic structure principles1. Issue 35 (21st September 2015) - Morales-Bayuelo, Alejandro; Pan, Sudip; Caballero, Julio; Chattaraj, Pratim K.
<x xml:space="preserve">Abstract</x> The phenomenon of torquoselectivity in electrocyclic ring opening reactions is explained through the electronic structure principles.